1978
DOI: 10.1139/m78-245
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium strain identification in Arachis hypogaea nodules by enzyme-linked immunosorbent assay (ELISA)

Abstract: The technique of enzyme-linked immunosorbent assay (ELISA) was used for serological identification of peanut Rhizobium strains both in cell suspension of pure culture and in single root nodules of groundnut (Arachis hypogaea) plants. Antisera of three peanut Rhizobium strains were tested against eight different Rhizobium isolates. Three serogroups identified by agglutination and immunodiffusion tests were confirmed by ELISA. In this experiment ELISA was more sensitive by four to six orders of magnitude than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 4 publications
2
25
0
1
Order By: Relevance
“…This result confirms those obtained by Graham (1981) and Amarger (1986) (Kishinevsky and Bar-Joseph, 1978;Ayanaba et al, 1986;Cleyet-Marel, 1987;Evans et al, 1996 (Cregan and Keyser, 1988) and white clover (Mytton, 1975 (Schuller et al, 1986;Heakman, 1987;Salez and Saint-Macary, 1987;Minchin et al, 1989) …”
Section: Preparation Of Antigens and Antiserasupporting
confidence: 87%
See 1 more Smart Citation
“…This result confirms those obtained by Graham (1981) and Amarger (1986) (Kishinevsky and Bar-Joseph, 1978;Ayanaba et al, 1986;Cleyet-Marel, 1987;Evans et al, 1996 (Cregan and Keyser, 1988) and white clover (Mytton, 1975 (Schuller et al, 1986;Heakman, 1987;Salez and Saint-Macary, 1987;Minchin et al, 1989) …”
Section: Preparation Of Antigens and Antiserasupporting
confidence: 87%
“…This can be accomplished by a number of procedures. Serotyping is the most commonly used method for Rhizobium identification (Kishinevsky and Bar-Joseph, 1978;Ayanaba et al, 1986;Cleyet-Marel, 1987;Wolff et al, 1991). (Vincent, 1970 (Beck et al, 1993) (Somasegaran and Hoben, 1985) (Fe(II)EDTA instead of Fe-citrate).…”
mentioning
confidence: 99%
“…The results of the testing of different ELISA procedures showed that the presented final ELISA test procedure gave maximum ELISA values. When applying the designed ELISA test with enzyme conjugate derived by whole-cell immunization it was possible to detect and recognize strains of rhizobia in samples containing 1 x loJ cells ml- (Table l), a concentration lower than in earlier reports (Kishinevsky & Bar-Joseph, 1978;Berger et al, 1979;Morley & Jones, 1980). Strain specificity of the ELISA test was also obtained in nodule extracts containing 1 x lo5 cells ml-I ( Table 3).…”
Section: Results a N D Discussionmentioning
confidence: 72%
“…Moreover, loss of antibiotic markers during growth makes this method unsuitable for strain identification. Serological techniques include agglutination, immunogel diffusion, immunofluorescence and ELISA, and have been used to identify Rhizobium japonicum grown in culture and from root nodules (Dudman, 1971; Kishinevsky and Bar Joseph, 1978; Olsen and Rice, 1989). However, cross reactive antigens present in other strains give faulty results and limit the use of these techniques (Vincent and Humphery, 1970).…”
Section: Introductionmentioning
confidence: 99%